Efek kehilangan figur ayah terhadap pembentukan identitas gender remaja - Maulana, Muhammad Dimas (Maliki Interdisciplinary Journal, 2025)
The phenomenon of fatherlessness (the physical or emotional absence of a father figure) is increasing in society, significantly impacting adolescent development, particularly gender identity formation. This article analyzes the relationship between father absence and the process of adolescent gender identity formation through a systematic literature review. Studies show that fathers play a crucial role as role models for boys in learning healthy masculinity and for girls in shaping expectations about relationships with men. Father absence (due to death, divorce, emotional disengagement, or employment) is associated with an increased risk of gender role confusion, deviant behavior, difficulties in social relationships, and identity crises, although the impact varies based on the child’s gender, age, social support, and cultural context. This article concludes that the presence of an active and loving father is a protective factor in the development of a healthy gender identity. This implies the need for strategies to strengthen family roles, utilize substitute figures (teachers, mentors, extended family), and policy interventions that support intact families or single parents. The study’s approach is based on a review of developmental psychology theories (Erikson, Bandura) and a synthesis of previous empirical research findings on this topic.